Attitudes towards Faculty Unions and Collective Bargaining in American and Canadian Universities - Katchanovski, Ivan; Rothman, Stanley; Nevitte, Neil (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2011)
This study analyzes attitudes towards faculty unions and collective bargaining among faculty and administrators in the United States and Canada. This is the first study which compares support for unionization and collective bargaining in American and Canadian universities among faculty members and administrators. The main research question is: Which factors are the determinants of attitudes towards faculty unions and collective bargaining in American and Canadian universities and colleges? Our hypotheses are that cultural, institutional, political, positional, socio-economic, and academic factors are significant predictors of support for faculty unionization. The academics in Canada are likely to be more supportive of faculty unionism compared to their American counterparts because of differences in national political cultures. Institutional and political factors are also likely to affect such views. This study uses comparative and regression analyses of data from the 1999 North American Academic Study Survey to examine attitudes towards unions and collective bargaining among faculty and administrators in the United States and Canada. The analysis shows that Canadian academics are more supportive of faculty unions and collective bargaining than their American counterparts. These results provide support to the political culture hypothesis. However, the study shows that institutional, political, positional, socio-economic and academic factors are also important in many cases. A faculty bargaining agent on campus is positively associated with favorable views of faculty unions and collective bargaining among American professors and with administrators’ support for collective bargaining in both countries. Administrators’ opposition is also important, in particular, for attitudes of Canadian faculty. Professors are more pro-union than administrators in both countries. Income, gender, race, age, religion, and academic field, are significant determinants of attitudes of faculty and administrators in the US and Canada in certain cases.